Some aspects of organizing prosecutor's supervision over the implementation of legislation in the forestry sphere - Mamadaliev Bakhtiyor Zakirovich (Emerging Frontiers Library for The American Journal of Political Science Law and Criminology, 2025)
This scientific article analyzes the key theoretical, legal, and practical aspects of organizing prosecutorial oversight for the precise and rigorous implementation of legislation in the forestry sector of the Republic of Uzbekistan. Special attention is given to identifying the characteristic features and problematic situations that arise during the execution of supervisory activities in this field. Moreover, the work substantiates relevant proposals and recommendations aimed at further optimizing and institutionally improving the mechanisms of prosecutorial oversight, taking into account the specifics of legal regulation, environmental factors, and strategic objectives of sustainable forest resource management within the context of national legislation and international commitments.